Review of agronomic research on the milpa, the traditional polyculture system of Mesoamerica - Fonteyne, Simon; Castillo Caamal, José B.; Lopez-Ridaura, Santiago; Van Loon, Jelle; Espidio Balbuena, Juan; Osorio Alcalá, Leodegario; Martínez Hernández, Fermin; Odjo, Sylvanus; Verhulst, Nele (Frontiers in Agronomy, 2023)
The milpa system is the basis of traditional agriculture in Mesoamerica. It is based on a polyculture of maize (Zea mays L.), bean (Phaseolus spp.) and squash (Cucurbita spp.) and is associated with a great diversity of crops and wild species. The milpa has great cultural and historical importance but can also be highly productive and provide sufficient and healthy diets for smallholder farmers. The milpa system is practiced less and less however, mainly due to socioeconomic changes, but also due to a lack of agronomic knowledge adapted to current conditions. To provide a starting point for new agronomic research, we reviewed the scientific literature to identify the current knowledge on milpa agronomy and determine research priorities to further improve the system. Given the wide diversity of conditions under which milpa is practiced, agronomic research is lacking, but indicates that improvements to the milpa can be made in all aspects of the milpa. 176 research articles on the milpa system were found in databases, of which 61 treated agronomic research. The main agronomic topics described in literature are crop variety, soil fertility management, weed management and productivity. Most research has focused only on maize and studies reporting on the associated crops are scarce. More research on all aspects of the milpa is needed to understand and improve the agronomy of the system under the changing conditions of modern agriculture. Reducing the workload associated with the milpa, as well as soil fertility and weed management can be identified as research priorities.